Peranan Kemampuan Manajerial Kepala Sekolah Dalam Rangka Meningkatkan Mutu Pendidikan Di Tingkat Sekolah Dasar Kecamatan Mandai Kabupaten Maros - Andi Nurochmah; M. Bachtiar; Syamsurijal Basri (Publikasi Pendidikan, 2017)
The problem in this research is how the school principals management ability in order to improve the quality of elementary school education in the District Mandai Maros?. The objective in the study is to describe the school principals management skills in order to improve the quality of elementary education in the District Mandai Maros. This research is quantitative descriptive, the population of all teachers and members of the study sample, only 60 teachers from elementary, data was collected using a questionnaire, documentation. Then the data is analyzed using percentages. The results showed that the competency of school principals average category both in terms of planning, organizing, Directing. Although in this element there are not enough in the maximum or category Briefing teachers who have difficulties in the learning process.Keywords: management ability, quality of education, principal